Politeness Strategies In Dialogue Characters John Wick Chapter 3 - I Nyoman Dika Adi Putra; I Made Yogi Marantika (JURNALISTRENDI : JURNAL LINGUISTIK, SASTRA, DAN PENDIDIKAN, 2024)
The aims of this study is to identify four aspects of politeness strategies, those.are.bald on record, positive and negative strategies, off record based on the theory of politeness strategies from Brown and Levinson (1987). The data were collected by several steps: downloading the movie, watching the movie, reading the script and identifying the utterances use by the characters in the movie. While the qualitative description was chosen as the method. The result of this study shows 34 data how the characters used the politeness strategies in the film John Wick Chapter 3. The data is classified according to the four types of politeness strategy, bald on record, positive and negative politeness, off record. Based on the results of the study In the film John Wick Chapter 3, understanding the various types of politeness strategies can help speakers and listeners understand each other and to achieve communication goals.